Concerning the status of mathematics and physics for secondary school science students’ sustainability in the 21st century STEM disciplines - Kibona, Isack E. (Frontiers in Education, 2026)
IntroductionThe National Examination Council of Tanzania plays a significant role in shaping secondary school graduates’ career pathways through the Certificate of Secondary School Education (CSEE). This study examined future implications and strategies for improving graduates’ prospects in Science, Technology, Engineering, and Mathematics (STEM) fields, using the 2022 CSEE results from secondary schools in Mbeya City.MethodsThe study analyzed data from 58 secondary schools in Mbeya City. Statistical tools, including tables, bar charts, and chi-square tests, were used to organize, analyze, and interpret the data.ResultsOut of approximately 7,900 students, about 19% were found to be eligible to pursue STEM-related careers, with nearly two-thirds originating from private schools. Approximately 500 girls participated in STEM subjects, with significantly higher participation from private schools; the number of participants from private schools was about four times that from public schools. Gender parity was observed in private schools, whereas boys outperformed girls in public schools. Physics recorded the lowest levels of both participation and performance, with approximately three times as many students from private schools as from public schools, despite the higher overall participation of public-school students in the CSEE. Mathematics and physics emerged as key enablers of STEM success.DiscussionThe findings highlight disparities in STEM participation and performance between public and private schools and underscore the critical role of subject selection in shaping STEM career pathways. It is therefore recommended that science students take both mathematics and physics in the CSEE, rather than the current practice in which mathematics is compulsory while physics remains optional.